2020
DOI: 10.1177/2158244019900173
|View full text |Cite
|
Sign up to set email alerts
|

Managing Diversity for Organizational Efficiency

Abstract: The article examined “managing diversity for organizational efficiency.” It sought to find out the extent to which diversity management influences organizational efficiency through the management of conflict, cultural diversity, and employees’ perception of marginalization as well as teamwork and employee work attitude. The survey design was employed. A sample of 178 respondents from nine multinational companies in south-south Nigeria was employed. Research data were analyzed using structural equation modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 15 publications
0
61
1
4
Order By: Relevance
“…Random sampling was employed in selecting the respondents. The sampling technique is consistent with Inegbedion and Obadiaru (2018) as well as Inegbedion et al (2019). Mix method, consisting of secondary and primary techniques, was used to generate the research data.…”
Section: Methodsmentioning
confidence: 99%
“…Random sampling was employed in selecting the respondents. The sampling technique is consistent with Inegbedion and Obadiaru (2018) as well as Inegbedion et al (2019). Mix method, consisting of secondary and primary techniques, was used to generate the research data.…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive definition of workforce diversity means heterogeneity and differences among employees in an organisation in terms of race, age, ethnicity, cultural background, physical abilities, religion, gender, sexual orientation, language, education, lifestyle, beliefs, appearance and economic status (Choi & Rainey, 2010;Manoharan & Singal, 2017;Pitts, 2009;Roosevelt Thomas, 1990;Inegbedion, Sunday, Asaleye, Lawal & Adebanji, 2020;Saxena, 2014). The scholars frequently use different terms to refer to DM, such as "equality at the workplace", "diverse workforce", "equal opportunities", and "inclusion".…”
Section: The Concepts Of Workforce Diversity Managementmentioning
confidence: 99%
“…It has been studied as a mediator of the relationship between diversity and performance (Cai et al, 2013; Ensley et al, 2002; Inegbedion et al, 2020), but also as a moderator since conflict can be focused on specific behaviors rather than on a general perception of difference resulting of heterogeneity (Janssen et al, 1999; Simons, 1995; Simons et al, 1999). In this sense, Simons et al (1999) found that the effects of conflict were stronger for more job-related forms of diversity as it stimulates constructive debate.…”
Section: Literature Reviewmentioning
confidence: 99%